Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10048-015-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

The fused in sarcoma protein forms cytoplasmic aggregates in motor neurons derived from integration-free induced pluripotent stem cells generated from a patient with familial amyotrophic lateral sclerosis carrying the FUS-P525L mutation

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that primarily affects motor neurons (MNs) and has no effective treatment. Mutations in the fused in sarcoma (FUS) gene and abnormal aggregation of FUS protein have been reported in ALS. However, the mechanisms involved in ALS are poorly understood. Clinical drug trails have failed due to a lack of appropriate disease models, including a lack of access to MNs from ALS patients. Induced pluripotent stem (iPS) cells derived from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
1
24
2
Order By: Relevance
“…In young, 21 days differentiated MNs, FUS was mainly localized in nuclei, except for the most aggressive mutation in which FUS was already translocated into the cytoplasm. In mature 42 days differentiated MN from control cell lines, FUS was not only localized in the nuclei (Japtok et al, 2015; Lenzi et al, 2015; Liu et al, 2015) but was also detectable as small punctae along the neurites. This observation was very similar to the FUS localization along neurites and within the presynaptic compartment in hippocampal neurons (Schoen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young, 21 days differentiated MNs, FUS was mainly localized in nuclei, except for the most aggressive mutation in which FUS was already translocated into the cytoplasm. In mature 42 days differentiated MN from control cell lines, FUS was not only localized in the nuclei (Japtok et al, 2015; Lenzi et al, 2015; Liu et al, 2015) but was also detectable as small punctae along the neurites. This observation was very similar to the FUS localization along neurites and within the presynaptic compartment in hippocampal neurons (Schoen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies using hiPS cell lines expressing different mFUS variants are published up to now showing a cytoplasmatic distribution of FUS in mFUS hiPSC derived spinal MN (Lenzi et al, 2015; Liu et al, 2015; Ichiyanagi et al, 2016; Naujock et al, 2016) and an enhanced recruitment of FUS into SGs after the induction of cellular stress. Similarly, in hiPSC-derived cortical neurons expressing different mFUS variants (a mild mutation R521C and an aggressive mutation R495QfsX527), cytoplasmic FUS inclusions were spontaneously formed and were dependent on both, the severity of the mutation and neuronal age.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the first ALS patient iPSC-derived motor neurons (MNs) were generated 4 . Since then, many ALS iPSC studies have been reported,4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 and this technology is leading to new findings and therapeutic candidates for ALS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of recently developed induced pluripotent stem cell (iPSC) technologies also enables understanding of the disease pathogenesis ( Mattis and Svendsen, 2011 , Okano and Yamanaka, 2014 ). Indeed, iPSCs have been generated from ALS patients with mutations in SOD1 ( Chestkov and Vasilieva, 2014 , Dimos et al., 2008 ), TDP-43 ( Bilican et al., 2012 , Egawa et al., 2012 ), C9ORF72 ( Almeida et al., 2013 , Sareen et al., 2013 ) and recent publications of FUS ( Lenzi et al., 2015 , Liu et al., 2015 , Di Salvio et al., 2015 ) suggest a useful tool for pursuing the cellular pathogenesis and mechanism underlying FALS.…”
Section: Introductionmentioning
confidence: 99%